The Ministry of Health (London : Co-operative Printing Society)
1919 1919 1910s 18 pages 3. In addition it should take over and co-ordinate other health services such as: — (a) Home Office. — Board of Control in relation to lunatics and feeble-minded, inebriates; alien immigration, lead, phosphorus, and other industrial poisoning; Factory Acts (eliminating therefrom the distinction between factories and workshops); (b) Board of Education. — The medical side of school work and of schools for mothers; (c) Privy Council. — Nominations to the Council governing the medical profession and midwives; (d) Ministry of Pensions. — Medical treatment of discharged and disabled sailors and soldiers; (e) Ministry of Munitions. — Continue the health functions performed by the Ministry during the war in connection with occupational diseases; (f) Certain services in other Departments which specifically relate to health. 4. Housing. — The Ministry of Health should have the supervision and control of the health aspect of housing. 3. Research. — One of the main duties of the Ministry of Health should be the direct prosecution of medical research by the Ministry and also its encouragement, financially and otherwise, in universities and other independent institutions. LOCAL ADMINISTRATION. The following suggestions are offered on the question of local administration: — The local authority should be the one Health Authority, but it is desirable that the local Health Committees should be reorganised and strengthened, especially by direct representation of the medical profession, in order that they may carry out efficiently the policy of the Ministry of Health. A cardinal principle of this policy should be the laying down of a national minimum, at the same time offering every encouragement to progressive authorities to go beyond this. Poor Law Authorities. — The health functions of these authorities, whether institutional or domiciliary, should be transferred to the local Health Authority. Insurance Committees. — The functions of the Insurance Committees should be transferred to the Health Authority. Local Government Areas. — As to areas for local health administration, the Sub-Committee agreed to the following policy: — 1. That clinical and curative medicine cannot be administratively divorced from preventive medicine, both being parallel and co-ordinate branches of State medicine. 2. That in regard to England and Wales (excluding London) the County Councils and County Borough Councils* be appointed by Parliament to be directly responsible to central Government Departments for all medical, sanitary, clinical, preventive, domiciliary, and institutional administration in *The duty of appointing a Health Committee, with such subcommittees as are found necessary or desirable, shall also be incumbent on such non-county boroughs or urban districts or combination of such as may be approved by the Ministry of Health, provided that the population of such an area shall not be less than 150,000. 15 36/H24/6